Expedient synthesis of a phenanthro-imidazo-pyridine fused heteropolynuclear framework via CDC coupling: a new class of luminophores. Issue 19 (27th March 2017) - Banerji, Biswadip; Chatterjee, Satadru; Chandrasekhar, K.; Bera, Suvankar; Majumder, Leena; Prodhan, Chandraday; Chaudhuri, Keya
Abstract : We herein report the design and synthesis of a group of fused phenanthro-imidazo[1, 2- a ]pyridine derivatives as a new class of luminescent materials through a Pd(ii ) catalyzed intramolecular CDC coupling. Abstract : We herein report the design and synthesis of a group of fused phenanthro-imidazo[1, 2- a ]pyridine derivatives as a new class of luminescent materials through a Pd(ii ) catalyzed intramolecular CDC (cross dehydrogenative coupling) reaction. This method thus unlocked a convenient & expedient way for the synthesis of a new molecular framework containing π-extended fused heteropolycycles. The heteropolycycles showed very good fluorescence properties both in solid and solution phases which were further utilized in live cell imaging. These kinds of molecules have potential to be used as therapeutic probes and also their solid state luminescence properties can be further utilized for making optoelectronic devices.